SOSIALISASI INOVASI PENGOLAHAN PRODUK BERBAHAN BAKU SINGKONG UNTUK MENINGKATKAN PENDAPATAN PETANI SINGKONG DI KABUPATEN MUSI RAWAS - Ira Primalasari; Vera Octalia (LPPM UNMURA, 2023)
The aim of this PKM is to increase knowledge about innovative processed cassava products that can be made into various kinds of food products, improve the skills of cassava craftsmen, empower people to be more productive, and create more modern processed cassava products to increase income. The location of this PKM activity was carried out in M. Sitiharjo Village, attended by 10 opaque, sweet potato cracker and eyek-eyek craftsmen. The stages of activities carried out at this PKM are the preparation stage. The enthusiasm of the participants in this PKM activity was felt when there was a question and answer session and sharing stories. The hardest thing felt by the cassava craftsmen was the marketing of processed opaque products. So that makes the opaque craftsmen not enthusiastics and not innovating to make new products. With this PKM activity, it is hoped that the craftsmen will be more enthusiastic and able to innovate fot the better